Tilapia nilotica Head Lipids Improved Bone Loss by Regulating Inflammation and Serum Metabolism Through Gut Microbiota in Ovariectomized Rats - Zhu, Yujie; Liu, Shucheng; Mei, Fengfeng; Zhao, Meihui; Xia, Guanghua; Shen, Xuanri (Frontiers in Nutrition, 2022)
Osteoporosis is a global healthy problem, and it is of great significance to replace the drugs with natural functional factors. In this study, we investigated anti-osteoporotic activity of lipids prepared from Tilapia nilotica fish head (THLs) in the ovariectomized osteoporosis rats. THLs are composed of neutral lipids (NL, 77.84%), phospholipids (PL, 11.86%) and glycolipids (GL, 6.47%). There were clear differences in the fatty acid composition of disparate components, and PL contains the most abundant Ω-3 polyunsaturated fatty acids. The results proved that THLs could improve bone microstructure, increase bone mineral density, and decreased bone resorption. In order to further illustrate the anti-osteoporotic mechanism, we analyzed the changes of gut microbial communities, pro-inflammation factors, serum metabolites and metabolic pathway. Further study on gut microbiota shown that THLs significantly decreased content of Alistipes in gut, and dramatically increased the beneficial bacteria such as Oscillospira, Roseburia and Dubosiella. Meanwhile, pro-inflammation factors of serum in OVX rats decreased significantly and metabolites were changed. Therefore, we speculated THLs improved bone loss through reducing inflammation, changing the metabolites and metabolic pathway such as arachidonic acid metabolism and primary bile acid metabolism etc. by altering of gut microbiota. The results indicated that THLs could be a functional factor with anti-osteoporotic activity.